Mitigating Destructive Fishing through the Optimization of Community-Based Coastal Surveillance as an Effort to Safeguard Maritime Security - Dao, Yunias; Yusnaldi, Yusnaldi; Kusuma, Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to enhance coastal community involvement in marine surveillance to prevent such practices, focusing on issue identification, analysis, and strategy development for sustainable maritime security. Through a qualitative approach and literature review, the research examines community participation in marine resource surveillance, identifies challenges and opportunities, and suggests ways to optimize coastal community surveillance. Findings emphasize the importance of community-based surveillance in combating destructive fishing. A participatory framework that integrates communities into surveillance, decision-making, and implementation of sustainable marine management marks a shift from top-down to inclusive bottom-up models, recognizing local knowledge as vital. The study concludes that optimizing community-based coastal surveillance is crucial for addressing destructive fishing and supporting sustainable maritime security in Indonesia, recommending further research to explore its implementation across various regions and socio-economic conditions.